Synergistic catalytic action of vanadia-titania composites towards the microwave-assisted benzoin oxidation - Ferretti, Francesco (2019)
Intensification of chemical processes according to the motto "faster, simpler, greener" is among the main concerns nowadays. One of the ways of intensification is the application of synergistic catalytic effects when the overall efficiency of a composite catalyst is much higher than the sum of the component activities. Here, we report on the preparation of synergistic catalytic materials by a simple and straightforward ball milling procedure. Oxidation of benzoin was selected as a model reaction to demonstrate the viability of the concept. For the V2O5-TiO2 (95 : 5) composite material, the synergistic effect is triggered by low power microwave irradiation with more than a tenfold jump in the catalytic activity in comparison to the activities of the individual components.